2021
DOI: 10.48550/arxiv.2112.14133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quasinormal Modes of Black Holes with Multiple Photon Spheres

Guangzhou Guo,
Peng Wang,
Houwen Wu
et al.

Abstract: For a static and spherically symmetric black hole, a photon sphere is composed of circular null geodesics of fixed radius, and plays an important role in observing the black hole. Recently, in an Einstein-Maxwell-scalar model with a non-minimal coupling between the scalar and electromagnetic fields, a class of hairy black holes has been found to possess two unstable and one stable circular null geodesics on the equatorial plane, corresponding to three photon spheres outside the event horizon. In this paper, we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 60 publications
(93 reference statements)
1
21
0
Order By: Relevance
“…Furthermore, the QNM frequency can also partly reveal the stability of spacetime geometry under small perturbations [86,87]. Hence, the study of QNM has become a concerned topic [88][89][90][91].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the QNM frequency can also partly reveal the stability of spacetime geometry under small perturbations [86,87]. Hence, the study of QNM has become a concerned topic [88][89][90][91].…”
Section: Introductionmentioning
confidence: 99%
“…In recent works [78,79], we found that the hairy black holes can also possess multiple photon spheres outside the event horizon, which have significant effects on the optical observation of black holes illuminated by the surrounding accretion disk, e.g., leading to bright rings of different radii in the black hole images [78] and significantly increasing the flux of the observed images [79]. Later, it showed that the effective potential for a scalar perturbation in the hairy black holes exhibits a double-peak structure [80]. In the eikonal limit, the extrema of the double-peak potential correspond to the photon spheres, around which long-lived and sub-long-lived quasinormal modes were found [80].…”
mentioning
confidence: 75%
“…Later, it showed that the effective potential for a scalar perturbation in the hairy black holes exhibits a double-peak structure [80]. In the eikonal limit, the extrema of the double-peak potential correspond to the photon spheres, around which long-lived and sub-long-lived quasinormal modes were found [80]. The appearance of the double-peak effective potentials naturally motivates us to search echo signals of perturbations in the hairy black holes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of two photon spheres can significantly affect the optical appearance of HBHs illuminated by the surrounding accretion disk, e.g., producing bright rings of different radus in the black hole images [88] and noticeably increasing the flux of the observed images [89]. Moreover, the effective potential for a scalar perturbation in the HBHs with two photon spheres was shown to exhibit a double-peak structure, leading to long-lived quasinormal modes [90] and echo signals [91]. It is worth noting that the existence of two photon spheres outside the event horizon has also been reported for dyonic black holes with a quasi-topological electromagnetic term [92] and black holes in massive gravity [93,94].…”
Section: Numerical Resultsmentioning
confidence: 99%